Analysis of the Potential for Religious Tourism Based on Religious Rituals at Sakyawanaram Monastery, Cianjur Regency - Patricia Putri Anindya; Prayogo Susanto (Darul Yasin Al Sys, 2026)
The growing public interest in religious tourism indicates a shift from purely recreational activities toward spiritual experiences, cultural values, and the pursuit of inner peace. In this context, Sakyawanaram Vihara in Cianjur Regency, West Java, Indonesia, offers a distinctive religious tourism attraction through its sacred water bathing ritual, which symbolizes physical and spiritual purification and attracts visitors from diverse religious backgrounds. This study aims to analyze the potential of ritual-based religious tourism at Sakyawanaram Vihara. This study employed a qualitative research approach, with data collected through observation, in-depth interviews, and documentation. Informants were selected using purposive sampling and consisted of temple administrators, religious leaders, local community members, and tourists. The analysis was guided by the 5A tourism components framework, comprising attraction, accessibility, amenities, accommodation, and ancillary services, and was further strengthened through SWOT analysis. The findings reveal that Sakyawanaram Vihara possesses substantial religious tourism potential due to its spiritual significance, distinctive architectural features, serene natural environment, and strong tradition of interreligious tolerance. The study concludes that the sacred water bathing ritual can serve as a strategic basis for developing religious tourism while maintaining the sacredness and authenticity of the site. The contribution of this study lies in extending the discourse on ritual-based religious tourism and offering practical implications for optimizing digital media promotion and infrastructure management without compromising the structural sacredness and cultural-religious integrity of the ritual.